2015
DOI: 10.1038/ki.2014.297
|View full text |Cite
|
Sign up to set email alerts
|

The urinary proteome and metabonome differ from normal in adults with mitochondrial disease

Abstract: We studied the extent and nature of renal involvement in a cohort of 117 adult patients with mitochondrial disease, by measuring urinary retinol-binding protein (RBP) and albumin; established markers of tubular and glomerular dysfunction, respectively. Seventy-five patients had the m.3243A>G mutation and the most frequent phenotypes within the entire cohort were 14 with MELAS, 33 with MIDD, and 17 with MERRF. Urinary RBP was increased in 29 of 75 of m.3243A>G patients, whereas albumin was increased in 23 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 86 publications
5
49
0
Order By: Relevance
“…A large-scale proteomic analysis of urine samples from adult patients with mitochondrial diseases showed that 75 of 117 participants carried the mtDNA 3243 A>G mutation 97 . Nearly half of the patients with this mutation had albuminuria and/or low-molecular-weight proteinuria, indicating that mtDNA 3243 A>G probably represents the most common mitochondrial disorder with renal involvement.…”
Section: Glomerular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…A large-scale proteomic analysis of urine samples from adult patients with mitochondrial diseases showed that 75 of 117 participants carried the mtDNA 3243 A>G mutation 97 . Nearly half of the patients with this mutation had albuminuria and/or low-molecular-weight proteinuria, indicating that mtDNA 3243 A>G probably represents the most common mitochondrial disorder with renal involvement.…”
Section: Glomerular Diseasesmentioning
confidence: 99%
“…Nearly half of the patients with this mutation had albuminuria and/or low-molecular-weight proteinuria, indicating that mtDNA 3243 A>G probably represents the most common mitochondrial disorder with renal involvement. Approximately half of the patients with this disorder presented with MIDD, whereas most of the remaining patients presented with MELAS or MERRF syndromes 97 .…”
Section: Glomerular Diseasesmentioning
confidence: 99%
“…It is well known that the neonatal kidney function is impaired compared with adults due to immature glomerular filtration and tubular function and reduced kidney perfusion pressure [16]. Moreover, mitochondrial diseases are associated with renal functional impairment, despite normal serum creatinine levels [17]. Magnesium sulfate is exclusively excreted from the body by the kidneys through free glomerular filtration [10].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney pathology is more frequently reported in children than in adult . The most common mitochondrial DNA (mtDNA) defects reported with a kidney phenotype during adulthood are the mutation m.3243A>G in the tRNA ‐leu gene associated to myopathy encephalopathy lactic acidosis and stroke (MELAS) syndrome and mtDNA large scale deletions associated to Kearns‐Sayre Syndrome . Rare single case reports have described supplemental point mutations, most of them involving tRNA genes .…”
mentioning
confidence: 99%
“…The most common mitochondrial DNA (mtDNA) defects reported with a kidney phenotype during adulthood are the mutation m.3243A>G in the tRNA ‐leu gene associated to myopathy encephalopathy lactic acidosis and stroke (MELAS) syndrome and mtDNA large scale deletions associated to Kearns‐Sayre Syndrome . Rare single case reports have described supplemental point mutations, most of them involving tRNA genes . Complex I is the most frequent mitochondrial respiratory chain complex involved in mitochondrial diseases and is associated with a wide range of clinical presentations in children and young adults .…”
mentioning
confidence: 99%